Edukasi dan Praktik Cuci Tangan Pakai Sabun di Desa Meunasah Manyang Kecamatan Ingin Jaya Kabupaten Aceh Besar - Hafni Zahara; Zuhra Yurianda; Putri Balqis (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Clean and healthy living behavior (PHBS) is a set of behaviors practiced on the basis of awareness as a result of learning that makes a person, family, group or community able to help themselves in the health sector and play an active role in realizing public health. Participants who attended this activity were 10 children. Health education activities are very beneficial in increasing knowledge about clean and healthy living behavior (PHBS) to children. This activity needs to be carried out more widely in order to increase children's knowledge about health.